1849 Vt. Acts & Resolves 26 - (:unkn) unknown (My University, 1849)
Prohibited the manufacture, sale, giving, or disposing of any instrument or weapon usually known as a slungshot, and prohibited the carrying any slungshot or similar weapon. Violators guilty of misdemeanor, punishable by fine not exceeding five hundred but not less than two hundred dollars, or imprisonment not exceeding two years.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS